Analyzing the Implementation of Shufʻah 'Preemption Rights' in the Legal System of Bangladesh within the Framework of Islamic Law - Ahm Ershad Uddın (İslam Medeniyeti Araştırmaları Dergisi)
The Shufʻah ‘preemption’ law, a significant component of Islamic Shari'ah law, safeguards the rights of land partners and neighbors. Originating in 622 AD, it has played a crucial role in Muslim empires for over 1400 years. In response to contemporary challenges, such as fragmented land transactions and decreasing per capita land availability, modernizing land management laws, including pre-purchase rights, is essential. This article examines the Shufʻah Law's dimensions and compares Bangladesh's current national legal framework. Pre-emption rights empower co-sharers to acquire land before others, with consent or waiver paving the way for third-party acquisition. In Bangladesh, three legal approaches to pre-emption exist: the Muslim Law Approach, the State Acquisition & Tenancy Act 1950 Approach, and the Non-agricultural Tenancy Act 1949 Approach. The research relies on the viewpoint of the Hanafi school, which holds significance in Bangladesh's family law owing to the widespread adherence of the majority to this specific Madhab. In addition, the study seeks to explore the legal standing of the right of pre-emption in Bangladesh through the lens of Islamic law, provide solutions to this matter, and assess the feasibility of integrating pre-emption law principles into contemporary land law practices.